The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1111/j.1749-6632.2009.04568.x
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Immunity and Cancer Stem Cells

Abstract: Self-renewing cancer stem cells (CSC) capable of spawning more differentiated tumor cell progeny are required for tumorigenesis and neoplastic progression of leukemias and several solid cancers. The mechanisms by which CSC cause tumor initiation and growth are currently unknown. Recent findings that suggest a negative correlation between degrees of host immunocompetence and rates of cancer development raise the possibility that only a restricted minority of malignant cells, namely CSC, may possess the phenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
127
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(130 citation statements)
references
References 135 publications
2
127
0
1
Order By: Relevance
“…In fact, proliferation of T cells was inhibited by coculture with autologous or allogeneic CICs, but not with FBS tumor cells. CIC-associated factors, such as TGF-b, IL-10, IL-13, galectin, and PDGE2, which can play a negative regulatory role in the induction of tumor reactive T cells, have been described (12)(13)(14) and, notably, shown to be shared with normal stem cells as well (30). The complexity of this issue is demonstrated by the evidence that none of the molecules described above have been found to be specifically expressed or upregulated in CICs that we have isolated in vitro (data not shown), in line with the results that have been previously published by our group for GBM (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, proliferation of T cells was inhibited by coculture with autologous or allogeneic CICs, but not with FBS tumor cells. CIC-associated factors, such as TGF-b, IL-10, IL-13, galectin, and PDGE2, which can play a negative regulatory role in the induction of tumor reactive T cells, have been described (12)(13)(14) and, notably, shown to be shared with normal stem cells as well (30). The complexity of this issue is demonstrated by the evidence that none of the molecules described above have been found to be specifically expressed or upregulated in CICs that we have isolated in vitro (data not shown), in line with the results that have been previously published by our group for GBM (10).…”
Section: Discussionmentioning
confidence: 99%
“…Cancer-testis Ags have been found to be expressed by mesenchymal stem cells and to regulate the epithelial-to-mesenchymal transition, a process involved in development of metastases; thus these Ags may possibly have a role in the stemness properties of cancer cells and could represent target molecules for immunotherapy (11). Nevertheless, antitumor immunity could be attenuated by tumor-related immunosuppressive mechanisms that have been described in association with CICs isolated from melanoma or GBM (12)(13)(14). These findings suggest that a detailed immunological characterization of CICs isolated from different human tumors is a relevant issue to design new CICtargeted immunotherapeutic interventions.…”
mentioning
confidence: 99%
“…Recently, ABCB5 Ć¾ malignant melanoma-initiating cells were found to modulate antitumor immunity by preferentially inhibiting IL2-dependent T-cell activation and promoting induction of regulatory T cells (14,16). Moreover, CD200 Ć¾ CSCs were found to suppress antitumor immunity by downregulating the expression of Th1 cytokines and costimulatory molecules, in ovarian cancer, melanoma, and leukemia (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that immunoevasion is restricted to CSCs, enabling them to survive in the host (13)(14)(15). Recently, ABCB5 Ć¾ malignant melanoma-initiating cells were found to modulate antitumor immunity by preferentially inhibiting IL2-dependent T-cell activation and promoting induction of regulatory T cells (14,16).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a novel type of CSCs, ABCB5 ? malignant melanoma initiating cells (MMIC) were reported refractory to current immunotherapeutic treatment strategies (Schatton and Frank 2009). And interestingly, CSCs derived from glioblastoma multiform patients could suppress immune responses by impeding T-cell proliferation and activation, inducing T-cell apoptosis and inhibiting the phagocytosis ability of MUs/microglia (Wei et al 2010a, b;Wu et al 2010).…”
Section: The Evolving Concept Of the Cancer Stem Cell Modelmentioning
confidence: 99%